Non-Recognition of the Indigenous Community in Malaysian Media: Perspectives from the Orang Asli and Stakeholders - Jamal, Marlina; Naghmeh-Abbaspour, Bita (Penerbit Universiti Putra Malaysia, 2020)
This study presents the findings of interviews conducted on the Orang Asli and stakeholders concerning the issue of representation of the community in media. The main objective of this research was to investigate the views and opinions of the community and stakeholders concerning the portrayal of the Orang Asli community in local newspapers. Interviews were conducted with members of non-governmental organizations (NGOs), personnel from the Department of Orang Asli Development (JAKOA), journalists from mainstream Malaysian newspapers and Orang Asli individuals.